Nanoprecipitation-suppressed ferrite transformation (γ → α) during tempering in a medium‑manganese steel. (15th March 2019) - Xu, Yuantao; Li, Wei; Zuo, Xunwei; Li, Yu; Zhang, Caiyi; Min, Na; Chen, Hao; Jin, Xuejun
Abstract: NiAl-type nanoparticles retained on phase interfaces in the first step of partitioning treatment, e.g. 610 and 630 °C/1 h (P610 and P630 ), could effectively hinder interface migration from austenite to ferrite during the subsequent tempering treatment (500 °C/2 h) due to pinning effect. The deduced pinning pressure from the dilatation results is consistent with that from the pinning theory calculation. When the nanoparticles were absent in the specimen treated at 650 °C/1 h (P650 ), the significant interface migration persisted before precipitation of NiAl-type nanoparticles (500 °C/1800s) and gradually disappeared after they precipitated (500 °C/3600 s), which confirmed that nanoprecipitation does suppress ferrite transformation by the pinning effect. Graphical abstract: Unlabelled Image